TMEM132A, a Novel Wnt Signaling Pathway Regulator Through Wntless (WLS) Interaction - Li, Binbin; Niswander, Lee A. (Frontiers in Cell and Developmental Biology, 2020)
Wnt signaling pathway plays indispensable roles in embryonic development and adult tissue homeostasis. However, the regulatory mechanisms involved in Wnt ligand trafficking within and secretion from the signal producing cells is still relatively uncharacterized. Here, we discover a novel regulator of Wnt signaling pathway called Transmembrane protein 132A (TMEM132A). Our evidence shows a physical and functional interaction of TMEM132A with the Wnt ligand transporting protein Wntless (WLS). We show that TMEM132A stabilizes Wnt ligand, enhances WLS-Wnt ligand interaction, and activates WNT signaling pathway. Our results shed new light on the cellular mechanism underlying the fundamental aspect of WNT secretion from Wnt signal producing cells.